ID: 17: GRAVES DISEASE INDUCED DILATED CARDIOMYOPATHY. Issue 4 (22nd March 2016) - Alkhawam, H; Vyas, N; Sogomonian, R; Al-khazraji, A; Kabach, M
Abstract : Introduction: Graves' thyrotoxicosis has many cardiovascular complications; however, the most cardiac complication is atrial fibrillation but rarely causes heart failure. Less than 1% develops dilated cardiomyopathy with impaired left ventricular systolic function. In this case report we describe a case of Graves' hyperthyroidism-induced reversible cardiomyopathy. Case presentation: 45 year old female with a history of previously treated Graves' disease who presented to hospital for altered mental status and severe hypoglycemia. The hospital course complicated by Atrial fibrillation with RVR. Patient states that recently started feeling fatigue, orthopnea, decrease exercise intolerance, lower extremities edema and distended abdomen. In emergency department, patient found to have hypotension and tachycardic. She was given IV fluids but her blood pressure didn't respond. Patient was started on Levophed for hypotension. Physical examination demonstrated impressive proptosis, positive jugular venous distension, irregular irregularity of her plus and +2 lower extremities edema . Patient found to have Graves storm (TSH: 0.07 uIU/ml, Free T4: 1.89 ng/dL, T3: 36.6 ng/dL, cortisol level: 59.36 Ug/dL). She was started on methimazole, steroids and lugols iodine drops. Hypoglycemia that she had most likely was related to lack of glycogen stores and increased metabolic demand with graces. After the patient stabilized, echocardiogram obtained which showed severe left ventricular dysfunction (LVEF 30%), bi-atrial dilatation, LV dilated, moderate MR and TR. So, patient was transferred to CCU for acute dilated cardiomyopathy secondary to graves storm. She was started on Lasix 40 mg IV then switched to 20 mg PO twice a day, Metoprolol 25 mg twice a day and Digoxin 0.125 mg daily and Apixaban 5 mg twice daily. Ophthalmology consulted for proptosis who recommended artificial tears, ocular lubricant and decompressionAbstract ID: 17 Figure 1 .